2019
DOI: 10.1038/s41419-019-1656-4
|View full text |Cite
|
Sign up to set email alerts
|

A juxtacrine/paracrine loop between C-Kit and stem cell factor promotes cancer stem cell survival in epithelial ovarian cancer

Abstract: Receptors tyrosine kinase (RTK) enable normal and tumor cells to perceive and adapt to stimuli present in the microenvironment. These stimuli, also known as growth factors, are important molecular cues actively supporting cancer stem cell (CSC) self-renewal and viability. Since in epithelial ovarian cancer (EOC) the expression of c-Kit (CD117) has been identified as a CSC hallmark, we investigated the existence of a tumor growth-promoting loop between c-Kit and its ligand Stem Cell Factor (SCF). SCF exists as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
27
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(28 citation statements)
references
References 72 publications
1
27
0
Order By: Relevance
“…SCF-kit is the complex composed by ligand SCF and tyrosine kinase receptor c-Kit. The gene c-Kit is a proto-oncogene that is subject to dysregulation and gain-of-function mutations and amplifications that promote tumorigenesis in a variety of tumor types 46 . However, c-Kit can also promote apoptosis and inhibit tumor growth in absence of SCF (stem cell factor) 47 .…”
Section: Discussionmentioning
confidence: 99%
“…SCF-kit is the complex composed by ligand SCF and tyrosine kinase receptor c-Kit. The gene c-Kit is a proto-oncogene that is subject to dysregulation and gain-of-function mutations and amplifications that promote tumorigenesis in a variety of tumor types 46 . However, c-Kit can also promote apoptosis and inhibit tumor growth in absence of SCF (stem cell factor) 47 .…”
Section: Discussionmentioning
confidence: 99%
“…In addition, CSCs may exert a strong immune suppressive effect by suppressing the Major Histocompatibility Complex (MHC) by macrophages in the TME, releasing the exosomal miRNAs miR-9 and miR-21, or by secreting VEGF that plays a pivotal role in tumor angiogenesis and suppression of T-cell maturation [ 35 ]. Mazzoldi et al [ 36 ] found that, the c-Kit ligand Stem Cell Factor (SCF), produced by M2 macrophages, may favor the immune escape of tumor cells in ovarian cancer. Similarly, ovarian CSCs and macrophages reciprocally interact through the WNT/β-catenin signaling, thereby contributing to tumorigenesis, invasiveness, and immune suppression [ 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…Two µg of the total RNA, extracted from spheroids with TRIzol Q16 reagent (Invitrogen, Carlsbad) was reverse transcribed and then subjected to PCR with enzymes and reagents of the RTplusPCR system (Eppendorf, Hamburg, Germany) using GeneAmpPCR 2720 (Applied Biosystems, CA, USA) 56 . The cDNAs were amplified with primers specific for mTOR (5′-GTCATCCAACGGGAATGCA-3′/5′- TGATCGGTTACCGTGATCAAAA-3′), GAPDH (internal control): (5′-CAGAACATCATCCTGCCTCT- 3′/ 5′-GCTTGACAAAGTG GTCGTTGAG-3′) 13 .…”
Section: Methodsmentioning
confidence: 99%
“…Extracted DNA (2 µl) was used for 45 cycles of amplification in 20 µl of reaction mixture under the following conditions: 95 °C for 30 s, 56 °C for 30 s, and 72 °C for 60 s 56 . The PCR products were subjected to electrophoresis using 2% agarose gel 56 .…”
Section: Methodsmentioning
confidence: 99%